2011
DOI: 10.1080/1359432x.2010.524411
|View full text |Cite
|
Sign up to set email alerts
|

Job demands–resources model in the context of recovery: Testing recovery experiences as mediators

Abstract: The aim of the present study was to extend the original Job Demands-Resources (JD-R) model by taking into account recovery as an important mediation mechanism between work characteristics and well-being/ill-health. Specifically, we examined whether recovery experiences-strategies promoting recovery-might have a mediating role in the JD-R model among 527 employees from a variety of different jobs. The results showed that psychological detachment fully mediated the effects of job demands on fatigue at work and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
253
3
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 222 publications
(284 citation statements)
references
References 57 publications
22
253
3
6
Order By: Relevance
“…Earlier studies have provided support for the validity of single item measures (e.g., Drolet & Morrison, 2001;Elo, Leppänen, & Jahkola, 2003). Concerning recovery, it has been shown that recovery from work measured with one item correlated highly with longer recovery scales, such as need for recovery (Kinnunen, Feldt, Siltaloppi, & Sonnentag, 2011).…”
Section: Recovery During Lunch Breaksmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have provided support for the validity of single item measures (e.g., Drolet & Morrison, 2001;Elo, Leppänen, & Jahkola, 2003). Concerning recovery, it has been shown that recovery from work measured with one item correlated highly with longer recovery scales, such as need for recovery (Kinnunen, Feldt, Siltaloppi, & Sonnentag, 2011).…”
Section: Recovery During Lunch Breaksmentioning
confidence: 99%
“…Second, although previous studies have demonstrated one item measures to be valid substitutes for longer scales (Drolet & Morrison, 2001;Elo et al, 2003;Fisher, Matthews, & Gibbons, 2016;Kinnunen et al, 2011) future research may benefit from using multiple item measures for lunchtime recovery and recovery experiences. Third, a further limitation concerning the measures is that our study relies solely on self-report measures and may therefore suffer from common method bias.…”
Section: Limitations Strengths and Suggestions For Future Studiesmentioning
confidence: 99%
“…Work-related rumination as a concept differs from the concept of psychological detachment in that it refers solely to the negative side of thinking about work during off-job time, e.g., concentrating on problems. Low psychological detachment predicts emotional exhaustion over time (Sonnentag et al, 2010) and mediates the relationship between job demands and fatigue at work (Kinnunen et al, 2011). Irritation including both cognitive and emotional aspects has been found to mediate the effects of social (also supervisor-related) stressors on depressive symptoms (Dormann and Zapf, 2002).…”
Section: The Role Of Personal Resources As Mediatorsmentioning
confidence: 99%
“…The mechanism facilitating recovery is conceptualised within the context of the Job Demands-Resources-Recovery model (JD-R-R; Kinnunen, Feldt, Siltaloppi, & Sonnentag, 2011) -which is an extension of the original Job-Demands Resources model (JD-R; Demerouti, Bakker, Nachreiner, and Schaufeli, 2001) -by considering recovery as a significant mediation mechanism that underlies the relationship between work characteristics and well-being. Kinnunen et al's (2011) JD-R-R model postulates that job demands (e.g.…”
Section: Hypothesis 1cmentioning
confidence: 99%
“…Kinnunen et al's (2011) JD-R-R model postulates that job demands (e.g. work pressure) inhibit recovery leading therefore to impaired health, whereas job resources (e.g.…”
Section: Hypothesis 1cmentioning
confidence: 99%